The Effect Of Price Discount On Purchase Decision Of Marketplace Shopee In Business Administration Faculty Of Social And Legal Science State University Of Makassar College Students - Subhan, Syamsu; Baharuddin, Aris; Halim, Didin (Jurnal Administrasi Bisnis, 2025)
This study aims to determine how much influence Price Discounts have on Purchase Decisions on the Shopee Marketplace for Business Administration Students, Faculty of Social Sciences and Law, Makassar State University. This study uses a quantitative descriptive method. Data collection techniques include observation, questionnaires and documentation. The population is 470 people. The sampling method is using proportionate stratified random sampling method, so that the sample obtained is 83 people. The results of the analysis of the data obtained were processed using the SPSS 26 application which consisted of testing the validity and reliability of instruments, descriptive and inferential data analysis techniques.Based on the results of the study, it shows that the Price Discount variable is in a very good category with supporting indicators, namely the amount of the discount, the period of the discount and the type of product that gets the discount. The Purchase Decision Variable is in the very high category, because most of the respondents agree on the indicators of product choice, choice of brand, determination of the time of purchase and the situation at the time of purchase. Based on a simple linear regression test of 0.653 which shows that the direction of the relationship between the Price Discount variable and the Purchase Decision variable is unidirectional, the coefficient of determination test for the R2 value of 0.455 indicates that Price Discounts affect Purchase Decisions on the Shopee Marketplace for Business Administration Students, Faculty of Social Sciences and University Law Makassar State.. Keywords: Price Discount, Purchase Decision, Marketplace, Shopee